2017
DOI: 10.1093/ee/nvx084
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Topography of the Ailao Mountains on Congregated Landings of Airborne Sogatella furcifera (Hemiptera: Delphacidae) Populations

Abstract: The Sogatella furcifera (Horváth) is an important migrating rice pest whose outbreak may be caused by large-scale congregated landings. Hitherto, the meteorological factors that influence congregated landings were thought to be rainfall and downdraft. However, for migratory insects on a plateau, low temperature may be another key factor leading to congregated landings. However, no reports have been published. Therefore, this paper evaluates the reason for a large-scale congregated landing in the mountainous ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The authors believe that the continuous migration observed in the current study may well represent the short-range migration form of S. furcifera in Yunnan under normal circumstances, as reported by other research (Hu 2013; Zheng et al 2014b; Li et al 2017a,b; Wang et al 2017; Wu et al 2017). This migration pattern is remarkably different from some previously reported cases in a few localities in Yunnan and South to East China, which were characterized by a large abrupt immigration of macropterous adults in a very short period of time (e.g., overnight) and from a very distant source (Shen et al 2011, 2016; Jiang et al 2012; Wu et al 2012; Zhao et al 2014; Bi et al 2017; Hu et al 2017). Such migration events in South and East China are facilitated by flat terrain as mentioned previously; but in Yunnan, they are probably caused by occasional weather events or special terrain features (which may promote landings).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The authors believe that the continuous migration observed in the current study may well represent the short-range migration form of S. furcifera in Yunnan under normal circumstances, as reported by other research (Hu 2013; Zheng et al 2014b; Li et al 2017a,b; Wang et al 2017; Wu et al 2017). This migration pattern is remarkably different from some previously reported cases in a few localities in Yunnan and South to East China, which were characterized by a large abrupt immigration of macropterous adults in a very short period of time (e.g., overnight) and from a very distant source (Shen et al 2011, 2016; Jiang et al 2012; Wu et al 2012; Zhao et al 2014; Bi et al 2017; Hu et al 2017). Such migration events in South and East China are facilitated by flat terrain as mentioned previously; but in Yunnan, they are probably caused by occasional weather events or special terrain features (which may promote landings).…”
Section: Discussionsupporting
confidence: 86%
“…The white-backed planthopper, Sogatella furcifera (Horváth), is a serious pest on Asian cultivated rice, Oryza sativa L. in South China and North Indochina (Catindig et al 2009; Cheng 2009, 2015). Migratory behavior, high fecundity, and exponential population growth are the main causes of disastrous yield loss as well as the difficulty in performing accurate forecast and effective prevention (Gui et al 2008; Cheng 2009; Hu et al 2014, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This paddy was moderately fertile and was maintained with routine cultural practices, and no pesticide was used during the rice-growing season. Systematic field investigation of BPH population was performed once every 3 d by a plant-shaking method [11, 21].…”
Section: Methodsmentioning
confidence: 99%